Nurturing Capacity in Developing Countries : From Consensus to Practice - Nair, Govindan G. (World Bank, Washington, DC, 2012)
There is an emerging consensus that capacity building in developing countries must shift from supply-side, donor-driven to demand-led approaches. Three areas in which this is critical are evaluation capacity, the availability of skilled individuals, and aid management. An effective demand-led approach requires fostering a transparent evaluation culture, focused on poverty impacts and involving participatory approaches. The approach to skilled resources must move from skills acquisition to the retention and use of skills, using the resources of the diaspora, tackling incentives and addressing issues that discourage retention of skills.